Species of Metarhizium anisopliae complex implicated in human infections: retrospective sequencing study. (December 2017) - Nourrisson, C.; Dupont, D.; Lavergne, R.-A.; Dorin, J.; Forouzanfar, F.; Denis, J.; Weeks, K.; Joubert, R.; Chiambaretta, F.; Bourcier, T.; Roux, S.; Sénéchal, A.; et al.
Abstract: Objectives: Fungi belonging to the Metarhizium anisopliae complex comprise ubiquitous arthropod pathogenic moulds used as mycopesticides. Rare cases of human infections due to M. anisopliae have been reported. We hypothesize misidentifications of fungal strains implicated in these cases or used in mycopesticides. Methods: A review of the literature was conducted to identify previously published cases. We collected some of these previous described strains and reported new cases, and a French mycopesticide containing M. anisopliae . All identifications were performed based on elongation factor-1α gene sequencing. Results: We report eight new cases of Metarhizium infection in humans (three from France and five from Australia). The strains isolated from these cases, and three others from already published cases and reported as M. anisopliae, were molecularly identified based on elongation factor-1α ( Ef1-α ) gene sequencing as follows: Metarhizium robertsii (six), Metarhizium guizhouense (three), Metarhizium brunneum (one) and Metarhizium pingshaense (one). Conclusions: In this study, we report new human cases of Metarhizium infections, and, based on Ef-1α gene sequencing, we demonstrate the misidentification of species in case reports. We also correct the species identification of a strain reported as M. anisopliae used in a commercially available mycopesticide. According to our results, none of the strains from the human infection reports reviewed belongs to the species M. anisopliae .